1976
DOI: 10.1103/physreva.13.958
|View full text |Cite
|
Sign up to set email alerts
|

Kx-ray production cross sections for fourteen elements from calcium to palladium for incident carbon ions

Abstract: Absolute K-shell x-ray production cross sections for thin Ca, Sc, Ti, V, Fe, Ni, Cu, Zn, Ge, Rb, Sr, Y, Zr, and Pd targets have been measured for incident carbon ions in the energy range from 8 to 36 MeV. Ionization cross sections are calculated from atomic K-shell Quorescence yields and compared to the theoretical predictions of the plane-wave Born approximation including binding energy, Coulomb deflection, and relativistic corrections. K&/KP ratios and the shifts in the characteristic Ku and KP energies indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…a factor of 1.6 for Cu). Similar results were obtained by Wheeler et al [15] using 12C particles. Taking into account relativistic effects in the matrix elements they found good agreement between experiment and PWBABC theory.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…a factor of 1.6 for Cu). Similar results were obtained by Wheeler et al [15] using 12C particles. Taking into account relativistic effects in the matrix elements they found good agreement between experiment and PWBABC theory.…”
Section: Resultssupporting
confidence: 93%
“…The effective lowering of the target electron binding caused by the polarization effect leads to a strong increase of the K-shell ionization cross section. Several authors [1,15] found this increase to be proportional to (Z2/Z O-3 Figure 3 gives a summary of our measured ionization cross sections by a~N bombardment represented as a function of the corrected energy parameter qK/(e O~) 2. For comparison heavy ion results of Gray et al [12] and Brandt [1] are included for both groups Z2/Z~>2 and Zz/Zl<=2, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The applicability of the Coulomb ionization models to atomic encounters with projectiles heavier than alpha particles is still an open question, because the approximation of a small pertubation that is inherent to these models becomes doubtful. However, it has been shown that the corrected PWBA predicts ionization cross sections that are in fair agreement with measurements of K-shell ionization by heavier projectiles as 7Li [11], 11C [12,13], 14N [12], 160 [12,14] and 19F [15] though the requirement ZI~Z 2 is not generally valid in these cases. The purpose of this work has been to undertake systematic studies of target K-shell ionization induced by oxygen projectiles (160 and 1sO) on 16S, 19 K, 22Ti, 23 v, 24Cr, 25Mn, 26Fe, 27 CO, 28Ni, 29 Cu, 3oZn, 3zGe and 3sBr.…”
Section: Introductionmentioning
confidence: 94%
“…The purpose of this work has been to undertake systematic studies of target K-shell ionization induced by oxygen projectiles (160 and 1sO) on 16S, 19 K, 22Ti, 23 v, 24Cr, 25Mn, 26Fe, 27 CO, 28Ni, 29 Cu, 3oZn, 3zGe and 3sBr. The projectile energy range (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and the range of target elements studied, are in the intermediate region between the strict validity region of Coulomb ionization theories and that of the electron promotion model [2]. Apart from ionization cross sections we report also Ko]K p intensity ratios and K~-and KFline shifts as function of target atomic number and incident projectile energy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the production of K X-rays by heavy ions (such as 12 C or 16 O) was studied by several authors (Gray et al, 1976;Wheeler et al, 1976;Knaf et al, 1977;Zelazny and Hornshoj, 1984;Paul and Muhr, 1986;Geretschla¨ger and Benka, 1986;Geretschla¨ger et al, 1990;Geretschla¨ger et al, 1992;Fazinic et al, 1996;Tong et al, 1996;Sun et al, 1996;Mitra et al, 1997;Kubala-Kukus et al, 1999;Ozafra´n et al, 2003). Nevertheless, the development of theoretical models that describe and predict the X-ray production cross sections by heavy ion impact has not seen a strong advancement in the past 10 years, at least (Montenegro and Sigaud, 1985;Benka et al, 1987).…”
Section: Introductionmentioning
confidence: 96%